2018
DOI: 10.1208/s12249-018-1091-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of FT-NIR Analysis for In-line and Real-Time Monitoring of Pharmaceutical Hot Melt Extrusion: a Technical Note

Abstract: Continuous manufacturing, a gaining interest paradigm in the pharmaceutical industry, requires in-process monitoring of critical process parameters to ensure product consistency. This study demonstrated the application of Fourier transform near-infrared (FT-NIR) spectroscopy in conjunction with chemometrics modeling for in-line hot melt extrusion process monitoring. The obtained results suggested that inline FT-NIR analysis, along with a tailored NIR reflector, is a viable process analytical tool to monitor ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The study showed the in-line NIR was able to provide chemical information such as the blending ratio and interactions between the API and polymer, as well as physical properties of the sample such as color, temperature, and density. As NIR is a non-destructive and fast monitoring tool, it can also be used for both product development and manufacturing (143).…”
Section: In-line Process Monitoring Tools To Improve Processing Parammentioning
confidence: 99%
“…The study showed the in-line NIR was able to provide chemical information such as the blending ratio and interactions between the API and polymer, as well as physical properties of the sample such as color, temperature, and density. As NIR is a non-destructive and fast monitoring tool, it can also be used for both product development and manufacturing (143).…”
Section: In-line Process Monitoring Tools To Improve Processing Parammentioning
confidence: 99%
“…It is difficult to use KF as an analytical method to analyze the time-dependent characteristics of water absorption since the analytic procedure is not simple and is destructive. On the other hand, NIRS has recently been used quantitatively in the quality control of pharmaceutical preparations, [9][10][11][12][13][14][15][16][17] quantification of active pharmaceutical ingredients or excipients, 12,15,16) and measurement of the water content in food, pharmaceutical, and industrial products. 9,10,[18][19][20]22) NIRS is more advantageous and user-friendly than KF as it is a simple, rapid, nondestructive analytical method.…”
Section: Regular Articlementioning
confidence: 99%
“…e selected spectral scanning range was 12000-4000 cm − 1 , and the measured characteristics were the fundamental frequencies of molecular vibration, particularly the frequency doubling and combined frequency absorption bands of the stretching and bending vibration [36][37][38][39].…”
Section: Nir Spectral Featuresmentioning
confidence: 99%